Variations in Diffusion Coefficients on Equinox Days at Specified Critical Heights of the Ionosphere at the Equator - Kurt, Kadri; Yeşil, Ali (My University, 2024)
This study investigates the local time diffusion coefficient for stable and unstable ( , ) states at the equator (00), \"the geographical latitude where the first peak of the magnetic equatorial trough in the ionosphere occurs,\" during the spring and fall equinoxes (March 21 and September 23). The findings show that the diffusion tensor in a steady state is completely real and has a magnitude equal to the speed of light in a steady state. But in the unsteady state, the diffusion tensor consists of two parts, real and imaginary. The diagonal elements of the real part tensor are of the size of the conductivity in the ionosphere and the elements of the imaginary part are of the size of the speed of sound with about the same magnitude. Furthermore, for all assumed conditions, the diffusion elements form the first peak of the magnetic equatorial trough at 6.00 am local time.
Keywords: Diffusion Coefficient; Diffusion Tensor; Ionospheric Plasma